International Financial Statistics, April 2018. (International Financial Statistics; International Financial Statistics ;, 2018)
This paper discusses that for each quarter, the IMF prepares a financial transactions plan, in which it indicates the amounts of particular currencies and SDRs to be used during the relevant period. The IMF selects the currencies of members with strong balance of payments and reserve positions. It also seeks to promote, over time, balanced positions in the IMF. The effects of IMF transactions and operations are summarized in the IMF's holdings of members' currencies and in two other measures: reserve position in the IMF, and total IMF credit and loans outstanding. The IMF's holdings of a member's currency reflect, among other things, the transactions and operations of the IMF in that currency. This concept is used in calculating the amounts that a member can draw under tranche policies and in respect to certain of its obligations to the IMF.